Time dependent EC ', ECE and EC2E mechanisms at microdisc electrodes: simulations using adaptive finite element methods - Harriman, K; Gavaghan, D; Suli, E (2004)
In this paper we extend the work in [Electrochem. Commun. 5 (2003) 519] to more complex reaction mechanisms. We use the adaptive finite element algorithm described there to simulate the chronoamperometric current for EC′ reaction mechanisms (catalytic reaction mechanisms) at inlaid and recessed microdisc electrodes and for ECE and EC2E reaction mechanisms at microdisc electrodes. © 2004 Elsevier B.V. All rights reserved.